Experiences and self-care efforts among female sex workers in Nairobi, Kenya, during COVID-19 - Emily Nyariki; Mamtuti Panneh; Rhoda Wanjiru; Pooja Shah; James Pollock; Hellen Babu; Mary Kungu; Alicja Beksinka; Jennifer Liku; Joshua Kimani; Janet Seeley; Tara S. Beattie (Social Sciences and Humanities Open)
Background: Although the COVID-19 measures were aimed at the public good, they resulted in massive economic disruptions. We explored female sex workers’ (FSWs) experiences and self-care efforts following the deployment of COVID-19 containment measures in Nairobi, Kenya. Methods: Forty-seven women drawn from 1003 FSWs enrolled in the Maisha Fiti Longitudinal Mixed-Methods Study participated. An in-depth interview tool was used to capture FSW’ experiences and coping strategies during the COVID-19 pandemic after the Kenya government imposed containment measures that affected work, parenting, alcohol and substance use, exposure to violence, reproductive health service utilization, and mental health. All interviews were audio-recorded and transcribed verbatim. The data were thematically analysed and managed using Nvivo 12 software. Results: The findings show that FSWs suffered major economic loss following the COVID-19 containment measures that limited their movements and locked them out of sex work locations. Being mothers and daily wage earners, women reported challenges actualizing self-care goals for themselves and their children. Due to income loss, increased vulnerability to food and housing security, and mental distress were commonly reported. Specific behavioural actions to prevent contracting COVID-19 in the context of sex work were limited, due to women's inability to maintain social distance from clients. Conclusion: While the COVID-19 containment measures were intended to protect the public's health, they resulted in significant economic disruption for FSWs, which affected their ability to care for themselves and their children. Addressing the social determinants of sex work and discriminatory exclusionary practices is important for meeting the self-care needs of marginalised populations, especially FSWs and their families.